On the couch with Huizinga: Critical self-portrait assuming the work of art as plot for aesthetical reflection: (Palíndromo, 2021)
It is intended to reflect on the process of analysis and criticism of works of art, within the real regimes of art history, assumed by the author, who conceives the works as grounds for aesthetic reflection. Starting from questions like “what motivates me / us?”, He aspires to weave a patchwork quilt that forms a critical self-portrait. Developing reflections on concepts such as beauty, enigma, interval, aesthetic enjoyment, transcendent, among others, provides a background on her performance and her values as an art historian, trying to respond minimally to what she thinks of her performance, to finally say that it is the images that call it.
Keywords: Transcendental art.; Critical self-portrait; Art history and regimes of truth; Art and aesthetic reflection